Kedudukan Hukum Islam Dalam Sistem Hukum Nasional - Author: Mardani (Jurnal Hukum IUS QUIA IUSTUM, 2009)
For the purpose of the development of national legal system, Islamic law has paid significant contribution, at least in terms of the spirit. During decades, Islamic law has experienced significant development. The opportunity for the penetration of more aspects of Islamic law into Indonesian legal system is in positive trend.Keywords: Islamic Law, Islamic/Religious Court, National Legal System